The Violation of Cooperative Principle In the Kindaichi Shonen No Jikenbo 20’th Anniversary Series Comic Vol.1 - Made Diah Padmawati; I G.A.G. Sosiowati (Program Magister Linguistik Universitas Udayana, 2021)
The purpose of this research was to determine the violation types of cooperative principle in the utterance between characters in the dialogue of Kindaichi Shonen No Jikenzbo 20th Series Comic Vol.1. This research used descriptive qualitative method. The data of this research are in the form of utterances between characters in the dialogue of Kindaichi Shonen No Jikenbo 20th Series Comic Vol.1. The method used to collect the data is observation method which refers to the tapping and note-taking techniques. The method used to analyze the data is pragmatic analysis method with heuristic technique. The result showed that there were four violation types of cooperative principle including: maxim of quantity, maxim of quality, maxim of relevance or relation and maxim of manner in the Kindaichi Shonen No Jikenbo 20th Series Comic Vol.1. The most frequently flouted maxim in the utterance between characters in the dialogue of Kindaichi Shonen No Jikenbo 20th Series Comic Vol.1 was maxim of quality. This indicates that the characters in the Kindaichi Shonen No Jikenbo 20th Series Comic Vol.1 often say something that is still doubtful. On the other hand, related to the three violations of maxims, it was found that the same number of violations occurred between maxim of quality, maxim of relation and maxim of manner.